Recent Findings in Social Phobia among Children and Adolescents - Hitchcock, Carla A. (2009)
Childhood social phobia (SP) is common and associated with varying forms of impairment. The cause of social anxiety disorder is often complex, involving both genetic and environmental factors. Shyness in young children may be a possible precursor to social anxiety later in life, although not the sole antecedent. Current assessment of childhood social anxiety includes psychometrically sound self report and clinician administered measures either specifically targeting SP disorder or including the construct as a subscale of a broader measure. The type of measure that is used most often depends on the purpose of the assessment, the setting, time constraints, and required training. Extant data support the efficacy of both psychosocial and pharmacological interventions, with response rates ranging from 50–80%. Further research is needed to clarify the developmental stages of SP, the psychometric properties of brief measures, as well as the efficacy of combined interventions.